Essentials of materials science and engineering - Askeland, Donald R.; Wright, Wendelin J. (Cengage Learning, 2014)
Provides students with an understanding of relationship between the structure, processing, and properties of materials. This title present the fundamental concepts of atomic structure and the behavior of materials and link them to the "materials" issues that students have to deal with when they enter the industry or graduate school